Ceiling effect of beclomethasone/formoterol/glycopyrronium triple fixed-dose combination in COPD: A translational bench-to-bedside study. (August 2021) - Rogliani, Paola; Ora, Josuel; Girolami, Andrea; Rossi, Immacolata; de Guido, Ilaria; Facciolo, Francesco; Cazzola, Mario; Calzetta, Luigino
Abstract: Background: Currently, data on the possible synergy of adding a LAMA to ICS/LABA combination are missing and no studies assessed whether triple therapy may induce ceiling bronchodilator effect. A translational study was performed to investigate the interaction between glycopyrronium bromide (GB) and beclomethasone dipropionate (BDP)/formoterol fumarate (FF) combination in human isolated airways and the effect on FEV1 and small airway resistance of BDP/FF/GB in COPD. Methods: The interaction of adding GB to BDP/FF combination was tested in vitro in medium and small airways via Bliss, Loewe, and Highest Single Agent models. The peak and trough effect on FEV1 and R5-R19 of salbutamol on top of BDP/FF/GB 100/6/12.5 μg FDC via extrafine formulation was investigated in severe COPD patients after two weeks of treatment. Results: GB plus BDP/FF elicited significant synergistic bronchorelaxation in medium and small isolated airways (overall maximal effect: +32% vs. additive effect). No significant (P > 0.05) improvement in R5-R19 was detected when salbutamol was administered on top of BDP/FF/GB 100/6/12.5 μg FDC (peak −0.12 ± 0.22 cmH2 O/L/s, trough −0.23 ± 0.25 cmH2 O/L/s). Salbutamol significantly (P < 0.01) increased FEV1 when administered on top of triple FDC (peak +145 ± 119 ml, trough +221 ± 111 ml). Conclusion: The synergistic interaction detected in vitro when adding GB to BDP/FF combination may lead to ceiling bronchorelaxation of small airways in vivo, an effect that may improve hyperinflation in subjects with small airway disease and, thus, explain the substantial clinical benefits of triple combination therapy administered via extrafine formulation in severe COPD patients. Study registration: ISRCTN94089001.